PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KETERLIBATAN KERJA KARYAWAN DENGAN ORIENTASI BUDAYA INDIVIDU SEBAGAI VARIABEL PEMODERASI - Daniel Joel Immanuel Kairupan (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2017)
In the process of managing human resources and to realize good organizational performance hence required adequate leadership. Because leadership is one of the most dominant factors in determining value and influencing culture within the organization. One of the existing the leadership styles is transformational leadership. This leadership believed to affect the level of employee engagement. In addition, employee job involvement in work is also influenced by the orientation of individual cultures. This researce aims to examine the effect of transformational leadership on employee engagement. It also examines the effects of power ranges, collectivism, feminism, and the avoidance of uncertainty in moderating between in the influence of transformational leadership and employee engagement. The results show that there is influence of transformational leadership towards employee job involvement. Uncertainty avoidance is so found to positively moderate the influence of transformational leadership on employee job involvement. Meanwhile the range of power, collectivism, masculinity is not proven to moderate the relationship. Keyword: transformational leadership, job involvement, power ranges, collectivism, masculinity, avoidance of uncertainty.